THE INFLUENCE OF FACILITY, TIMELINESS AND TRUST WITH SATISFACTION AS INTERVENING VARIABLES TOWARDS LOYALTY OF EXECUTIVE TRAIN PASSENGERS OF SURABAYA GUBENG STATION - Firmansyah Firmansyah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Public transportation is the type of transportation that involves lives of The aims of this study is to determine and explain the simultaneous and partial influence of facilities, timeliness, trust through satisfaction as an intervening variable on the loyalty of Solo Balapan executive railroad passengers. The research method of this study was quantitative descriptive method. The population is all of train passengers in Gubeng executives. In this study data were collected by means of observation, interviews, questionnaires or questionnaires, literature study and documentation, and using the help of SPSS Statistics. This questionnaire was distributed to 100 respondents who were executive train users. The analysis used in this study includes data instrument tests (validity and reliability tests), multiple linear regression analysis, classic assumption tests (normality test, multicollinearity test, heteroscedasticity test) and hypothesis testing (F test, t test, coefficient of determination). The results of this study indicate that the variable facilities, timeliness, trust and satisfaction affect the loyalty of train passengers in Gubeng executives. T test results show the facility affects satisfaction of train passengers in Gubeng executives. Timeliness affects satisfaction of train passengers in Gubeng executives. trust affects satisfaction of train passengers in Gubeng executives. satisfaction affects loyalty of train passengers in Gubeng executives. Keywords: facilities, timeliness, trust, satisfaction and loyalty